Sevoflurane Intoxication: A Fatal Suicide - Efeoğlu Özşeker, Pınar; Çelik, Ebubekir Burak; Çam, Durdu Fatma; Koca Yavuz, Tuğçe (The Bulletin of Legal Medicine, 2023)
A 20-year-old female anesthesia technichian student was found dead lying on her back in dormitory room. The crime scene investigator reported that there was a 250 mL bottle labeled “sevorane liquid” on the table. During the autopsy, no traumatic injuries were found that could have caused the death. Histopathological evaluation of internal organs revealed focal areas of atelectasis and congestion in the lungs, autolysis and congestion in the pancreas, and congestion liver, heart, kidney, brain. Screening for drugs and their metabolites was conducted in blood, urine, and internal organs using enzyme immunoassays along with gas chromatography-mass spectrometry. Sevoflurane was identified and quantified using headspace gas chromatography, indicating a concentration of 41.0 µg/ mL in the blood. This substance was also confirmed in the gastric content through GC/MS analysis. It was reported that the death of the person occurred as a result of ingestion of sevoflurane and accompanying complications.